IMPACT OF MIXED SERVICE MARKETING PERFORMANCE AND CUSTOMER RELATIONSHIP MANAGEMENT ON PATIENT LOYALTY CASE STUDY: PRIVATE HOSPITAL, BANDUNG - Rahmah Zulkifli; Nunung Nurhayati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
Hospitals must deliver safe, timely, high-quality care while staying efficient and financially sustainable. Because healthcare is a credence service, patients often judge value from what they directly experience—communication, reliability of the service flow, waiting time, and facilities—rather than from technical outcomes. This study examined whether a hospital-adapted 9P service marketing mix and Customer Relationship Management (CRM) are associated with loyalty among corporate clients of a private women-and-children hospital in Bandung that showed declining utilisation and fewer corporate partners over one year. Using an explanatory cross-sectional design, data were collected from 125 employee-patients across 25 partner companies through five-point Likert questionnaires; scores were transformed using the Method of Successive Intervals (MSI) and analysed with descriptive statistics, Pearson correlations, and path analysis (). The 9P mix was rated fair-to-good (mean 3.39/5), strongest in staff appearance, professionalism, and core services, but weaker in promotion, price perceptions, punctuality/process reliability, and access cues. CRM was moderate-to-low (mean 2.85), with strong interpersonal communication but limited correspondence and rewards/privileges. Loyalty was moderate (mean 3.07): intention to return, cross-service use, and willingness to recommend were relatively strong, yet revisit frequency and feedback to management remained lower, indicating an intention–behaviour gap. In the path model, 9P significantly predicted loyalty (), whereas CRM did not (); together they explained 29.1% of loyalty variance (). The main implication is to improve point-of-care reliability first, then systematise CRM through scheduled follow-up, documented service recovery, and practical corporate benefits.